Study of Human Respiratory Functions in Relation to Crop Residue Burning - Awasthi, Amit (My University, 2011)
Human body is the most complex machine in which all the systems can be compared to various parts of the machine which work in a coordinated manner for the proper functioning of the body. As the machine requires energy from fuels, body also requires energy to do work which comes from food and oxygen. Along with fuel, if external material enters inside the machinery, proper functioning is affected which, after some time may stop working. Same thing happens in the case of human body; if external material along with food and air enters inside the body then health of the body is affected. These external materials are mainly the pollutants present in the air. Agriculture Crop Residue Burning (ACRB) plays a major role in causing pollution for a definite period. Crop residue burning activity is as old as human civilization and still considered as the cheapest and easy way of disposing off the agricultural waste. In present work, affect of ACRB on the ambient air and respiratory system of common healthy people were done by measuring their Pulmonary Function Tests (PFTs) like Force Vital Capacity (FVC), Force Expiratory Volume in first Second (FEV1), Peak Expiratory Flow Rate (PEF) and Force Expiratory Flow in 25 to 75% (FEF25-75%) etc. Ambient levels were considered by measuring the concentration levels of different size particulate matter like Suspended Particulate matter (SPM), Particulate matter of size less than 2.5 and 10 μm (PM2.5 and PM10). Study was carried out at the five sites of Patiala city of Punjab, India for three year of duration from February 2007 to January 2010, which included 50 healthy subjects. Age of 50 subjects lies between 13 to 53 years with mean value of 30 years. Subjects included 40 male and 10 female with mean height of 166 cm (139 - 179 cm) and weight of 62 kg (40 - 85 kg) at the start of the study. Standard methods of American Thoracic Society (ATS) were used to measure the PFTs by using portable Spirometer on the basis of which, subjects whose FEV1/FVC ratio larger than the 80 % were included in the study. Standard methods were used to measure the concentration of SPM and PM10 using High Volume Sampler (HVS) and Anderson Cascade Impactor (ACI). The results of three year study shows that there is a significant increase in the concentration level of different size particulate matter during the burning episode of wheat and rice crop residue. Rice crop residue burning has more effect on the concentration level in comparison to wheat crop residue burning. PFTs which are considered in the study shows ix significant decrease in their values during the ACRB, which is not recovered completely, even after the completion of burning episodes. Linear regression technique was used to authenticate the effect on the volume of air i.e., FVC and FEV1 was more during ACRB in comparison to other PFTs. Whereas, oxygen saturation level shows no significant change during the burning period of agriculture crop residue. Effect on the PFTs was more during the rice crop residue burning in comparison to wheat crop residue burning period. The maximum effect was observed on the lower and upper age groups as compared to the middle aged group. Contribution of different size particulate matter conclude that effect of smaller size particulate matter (PM2.5) is found to be higher in comparison to larger size particulate matter due to their greater penetration potential. The present study clearly signifies that ACRB is still a common process which reduced the ambient air quality that poses effects sometime permanent in nature on the PFTs of healthy subjects. Different analyses prove that rice crop residue burning has more effect on the lower and upper age groups due to increase in the concentration level of the particulate matter during the burning episodes. However, the middle age group is affected to a relatively less extent.
Keywords: Human Respiratory Functions